2014
DOI: 10.1097/bot.0b013e3182a2968e
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Delayed Operative Intervention in Displaced Clavicle Fractures

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 11 publications
0
14
1
1
Order By: Relevance
“…This may be related to earlier fracture healing and early rehabilitation after ORIF, which is known to be a critical factor for functional restoration of the shoulder girdle. One study revealed no statistically significant differences in any of the functional outcome evaluation methods between early and late fixation of displaced midshaft clavicular fractures, and the authors suggested that operative intervention for clavicle fractures between 3- and 12-week postinjury may be safe with no risk of excess complications [ 15 ]. However, our study results indicated improved functional restoration with ORIF for patients aged 30–65 years old, which may assist patients in returning to their preinjury social function, quality of life, and activity level in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to earlier fracture healing and early rehabilitation after ORIF, which is known to be a critical factor for functional restoration of the shoulder girdle. One study revealed no statistically significant differences in any of the functional outcome evaluation methods between early and late fixation of displaced midshaft clavicular fractures, and the authors suggested that operative intervention for clavicle fractures between 3- and 12-week postinjury may be safe with no risk of excess complications [ 15 ]. However, our study results indicated improved functional restoration with ORIF for patients aged 30–65 years old, which may assist patients in returning to their preinjury social function, quality of life, and activity level in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Early identification of patients at increased risk of nonunion following nonoperative treatment for targeted fixation is an emerging strategy from recent evidence. 25 - 28 …”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that delayed primary fixation in the first three months post-injury is a valid alternative without an apparent increase in complications [47][48][49] . Delayed recovery following non-operative management may predict union and can be accurately judged on a patient reported QuickDASH score and other objective clinical features at six weeks post-injury [ 50 , 51 ].…”
Section: Claviclementioning
confidence: 99%